Voluntary fasting to control post-Ramadan weight gain among overweight and obese women - Ismail, Suriani; Shamsuddin, Khadijah; Abdul Latif, Khalib; Abu Saad, Hazizi; A. Majid, Latifah; Mohd Othman, Fadlan (Sultan Qaboos University, 2015)
Objectives: This study aimed to examine the effectiveness of an Islamic voluntary fasting intervention to control post-Ramadan weight gain. Methods: This study was conducted between July and November 2011. Two weight loss intervention programmes were developed and implemented among groups of overweight or obese Malay women living in the Malaysian cities of Putrajaya and Seremban: a standard programme promoting control of food intake according to national dietary guidelines (group B) and a faith-based programme promoting voluntary fasting in addition to the standard programme (group A). Participants' dietary practices (i.e., voluntary fasting practices, frequency of fruit/vegetable consumption per week and quantity of carbohydrates/protein consumed per day), body mass index (BMI), blood pressure, fasting blood high-density lipoprotein cholesterol (HDL-C) and total cholesterol (TC):HDL-C ratio were assessed before Ramadan and three months post-Ramadan. Results: Voluntary fasting practices increased only in group A (P <0.01). Additionally, the quantity of protein/carbohydrates consumed per day, mean diastolic pressure and TC:HDL-C ratio decreased only in group A (P <0.01, 0.05, 0.02 and <0.01, respectively). Frequency of fruit/vegetable consumption per week, as well as HDL-C levels, increased only in group A (P = 0.03 and <0.01, respectively). Although changes in BMI between the groups was not significant (P = 0.08), BMI decrease among participants in group A was significant (P <0.01). Conclusion: Control of post-Ramadan weight gain was more evident in the faith-based intervention group. Healthcare providers should consider faith-based interventions to encourage weight loss during Ramadan and to prevent post-Ramadan weight gain among patients.